Applying an Artificial Neural Network to Predicting Effort and Errors for Embedded Software Development Projects - Iwata, Kazunori; Nakashima, Toyoshiro; Anan, Yoshiyuki; Ishii, Naohiro (IntechOpen, 2011)
None